2021
DOI: 10.1074/jbc.ra120.016019
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of carnitine monooxygenase CntA substrate specificity, inhibition, and intersubunit electron transfer

Abstract: Microbial metabolism of carnitine to trimethylamine (TMA) in the gut can accelerate atherosclerosis and heart disease and these TMA-producing enzymes are therefore important drug targets. Here, we report the first structures of the carnitine oxygenase CntA, an enzyme of the Rieske oxygenase family. CntA exists in a head-to-tail a3 trimeric structure. The two functional domains (the Rieske and the catalytic mononuclear iron domains) are located > 40 Å apart in the same monomer but adjacent in two neighbourin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 67 publications
3
58
0
Order By: Relevance
“… Schematic of NADH photoactivation coupled with EPR used to monitor the electron transfer from NADH to the Rieske‐type, [2Fe‐2S] 2+ in Ab CntA variants (e.g. Ab CntA; PDB ID: 6Y8J) [9b] and subsequent, carnitine catalysis takes place at the monoFe (where EPR‐silent, ferrous center is converted into high‐spin, ferric species; S =5/2) when the photo‐reduced, Ab CntA‐WT sample was annealed at higher temperatures (more details; see Figure 4). …”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“… Schematic of NADH photoactivation coupled with EPR used to monitor the electron transfer from NADH to the Rieske‐type, [2Fe‐2S] 2+ in Ab CntA variants (e.g. Ab CntA; PDB ID: 6Y8J) [9b] and subsequent, carnitine catalysis takes place at the monoFe (where EPR‐silent, ferrous center is converted into high‐spin, ferric species; S =5/2) when the photo‐reduced, Ab CntA‐WT sample was annealed at higher temperatures (more details; see Figure 4). …”
Section: Figurementioning
confidence: 99%
“…[4][5][6] Several quaternary ammonium oxygenases have been identified in the last decade, and studies of their active-sites have been reported. [7][8][9] These enzymes comprise a reductase protein containing ferredoxin domain or Rieske [2Fe-2S] 2+ cluster, and an oxygenase protein containing a non-heme, mononuclear iron center (monoFe). [8,10] The carnitine oxygenase (CntA) and reductase (CntB) from Acinetobacter baumannii convert carnitine into TMA and malic-semi-aldehyde (MSA).…”
Section: Rieske-typeoxygenasescatalyzeawiderangeofreactionsinmentioning
confidence: 99%
See 3 more Smart Citations